2013
DOI: 10.1037/a0028109
|View full text |Cite
|
Sign up to set email alerts
|

Tailored text messaging intervention for HIV adherence: A proof-of-concept study.

Abstract: The results demonstrate that using two-way text messaging to dynamically tailor adherence messages may enhance adherence and improve important clinical outcomes for PLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 20 publications
0
109
0
Order By: Relevance
“…The use of individually tailored information has been shown to be effective in promoting beneficial health behavior changes in adults in other contexts as well. 29,30,31 Although text messaging has been the most popular tool for facilitating behavioral interventions towards effective chronic disease self-care support, only a small percentage of American adults living with chronic diseases receives the benefits of text messaging for their health care support. 32,33,34 With advances in mobile health services and the widespread use of mobile phones in the Asian American population and in other ethnic minority populations, text messaging may be a powerful, costeffective way to facilitate communication between the patients and health care personnel, thereby improving health literacy and care disparity in ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of individually tailored information has been shown to be effective in promoting beneficial health behavior changes in adults in other contexts as well. 29,30,31 Although text messaging has been the most popular tool for facilitating behavioral interventions towards effective chronic disease self-care support, only a small percentage of American adults living with chronic diseases receives the benefits of text messaging for their health care support. 32,33,34 With advances in mobile health services and the widespread use of mobile phones in the Asian American population and in other ethnic minority populations, text messaging may be a powerful, costeffective way to facilitate communication between the patients and health care personnel, thereby improving health literacy and care disparity in ethnic minority populations.…”
Section: Discussionmentioning
confidence: 99%
“…The messages were first created based on input of experts, but a final phase of in-depth interviews with eight members of the target population were used to gather qualitative feedback on the messages (Lewis et al, 2013;Uhrig et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…There is increasing evidence that text message-based interventions are associated with short-term behavior change for health promotion, prevention, and disease management (Cole- Lewis & Kershaw, 2010). Studies have shown encouraging results across a range of health topics, including smoking cessation (Free et al, 2009;Whittaker et al, 2009), sexual and reproductive health (Lim et al, 2012), physical activity (Patrick et al, 2009), sun protection (Armstrong et al, 2009), medication adherence (Lewis et al, 2013), and risk reduction (Uhrig et al, 2012). Because health text messaging is relatively new, however, the evaluation of this technology has been limited.…”
mentioning
confidence: 96%
“…Findings from the outcome evaluation are reported separately. 22,23 2 • Participant Characteristics q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q q …”
Section: Intervention Implementationmentioning
confidence: 99%